New compounds with a dihydropyridine framework as promising hypolipidemic and hepatoprotective agents - Elena S. Ketova; Anna V. Myazina; Elena Yu. Bibik; Sergey G. Krivokolysko (Research Results in Pharmacology)
Introduction: To solve the problem of complex and safe pharmacological correction of metabolic disorders, including hyperlipidemia, hyperglycemia, and liver lesions is currently very important. With this in mind, the new derivatives of cyanothioacetamide with a dihydropyridine framework, with a potential effect on lipid and carbohydrate metabolism and the functioning of the liver are of great interest.